Rainwater Harvesting System Integrated With Sensors for Attic Temperature Reduction - Yew, Ming Chian; Wong, Song Wei; Yew, Ming Kun; Saw, Lip Huat (Frontiers in Built Environment, 2021)
This cool roof system focuses on utilization of rainwater harvesting systems by integrating the smart sensor to cool the roof and attic temperatures for the improvement of comfort level of building occupants. An ideal cool roof technology system is basically made up of these three components: (1) moving-air-cavity (MAC) ventilation, (2) solar-powered fan and (3) rainwater harvesting system. These three main components integrate to perform and control the cool roof system. Four small-scale cool roof models were designed and constructed to inspect the performance of the rooftop and attic temperatures. The experimental work was carried out indoors by employing the halogen lamp as the replacement for solar irradiation, while the ambient temperature is monitored to be around 29.8 °C throughout the test. The temperatures of the rooftop surface, MAC aluminium tube, and attic region were measured by K-type thermocouples to evaluate the performance of the cool roof designs. The solar-powered fans were incorporated into the MAC, which accelerated the airflow rate within the cavity and rejected the hot air out before transferring it to the attic region. Meanwhile, an innovative rainwater harvesting system was executed to cool the rooftop temperature rapidly by reducing the rate of heat transfer to the attic region. The result of this inventive cool roof system (Design Z) has successfully reduced the attic temperature by 10.8 °C compared to the normal metal deck roof model (Design W). The findings of the project revealed that the integrated cool roofing technology system comprises the ability to enhance the comfortability of building occupants towards a long-term sustainable development for a better world.